Study of impact of COVID-19 infection on ectopic pregnancy in a tertiary care center - Chavan, Niranjan N.; Rajput, Hitendrasing D.; Wade, Dinesh; ., Shikhanshi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: COVID-19 is an infectious disease caused by a recently discovered coronavirus (SARS-CoV-2). Most of the people infected with the coronavirus experience mild to moderate respiratory illness and recover without requiring any special treatment. In current study we have studied impact of COVID-19 pandemic on clinical outcome and management of ectopic pregnancy. Methods: Women with confirmed or suspected ectopic pregnancy admitted in emergency for further management and tested via nasopharyngeal (NP) or oropharyngeal swab for SARS-CoV-2 using reverse transcriptase polymerase chain reaction (RT-PCR) from April 1, 2020 to November 30, 2020 were included in the study. Results: In our study out of 32 case of ectopic pregnancy, 3 patients were COVID-19 positive. Total non COVID-19 patients were 29. Out of 32 ectopic pregnancies only 4 were unruptured ectopic pregnancy and rest 28 had ruptured ectopic pregnancy. Mortality among ectopic pregnancy was noted only in 1 case (3.12%). Conclusions: Timely diagnosis and initiating management at first point of care can reduce the morbidity and mortality due to ectopic pregnancy. Patient’s knowledge attitude and awareness will be achieved through health education. Women with clinical signs and physical symptoms of a ruptured ectopic pregnancy, such as hemodynamic instability or an acute abdomen, should be evaluated and treated urgently. In pandemic situation where some part of hospital facilities devoted to COVID-19 patients, so planned distribution of resources to tackle medical emergency will bear fruitful positive outcome.